Emory university telehealth neuropsychology development and implementation in response to the COVID-19 pandemic - Hewitt, Kelsey C.; Loring, David W. (Clinical neuropsychologist, 2020)
Objectives: Emory University has modified its clinical practices across specialties in response to the 2020 COVID-19 pandemic to provide service delivery while maintaining patient, staff, and faculty safety. This report shares current solutions and workarounds associated with telehealth neuropsychology (teleNP) while also recognizing teleNP opportunities. Results: We modified many measures from our traditional assessment protocols so they could be administered through Zoom. To maximize quality control, formal how-to coversheets and manuals were developed for both training and task administration (i.e. navigating Zoom assessment interfaces, practicing adapted test instructions, and troubleshooting). Conclusions: TeleNP has been successfully used to answer referral questions regarding deep brain stimulation (DBS) candidacy in Parkinson's disease patients and presence of mild neurocognitive impairment in patients with subjective memory decline. Our current protocols will continue to evolve with greater experience and are not considered to be a finished product. Nevertheless, development of robust teleNP protocols should expand availability of neuropsychology in both clinical and research applications while simultaneously decreasing assessment burden associated with traveling - sometimes long distances - for diagnostic neuropsychological evaluation.